A pluricentric view of Portuguese as a Non-Native Language teaching: the role of African, Macanese, and Timorese literatures - Albuquerque, Davi (2021)
Portuguese language is a pluricentric and international language, being one of the largest in the world, with native speakers and learners in several countries. However, the current Portuguese as a Non-Native Language (PNNL) teaching and its teaching materials focus one of the two existing Portuguese standards, European Portuguese or Brazilian Portuguese. Furthermore, given the scarcity of teaching materials that address the Portuguese language as pluricentric, we propose here a discussion and a guide for PNNL teaching using literary texts as authentic examples of different Portuguese linguistic norms along with intercultural and communicative teaching of Portuguese. Thus, after the introduction, we present a theoretical discussion on the subject followed by an example and a guide for elaboration. Finally, we point out some positive aspects and the impact on students regarding the use of this type of material.